Features of construction of acoustic reconnaissance equipment with their small overall dimensions - Олейников, А.Н.; Носулько, И.В. (Radiotekhnika, 2019)
A comparative analysis of the dependence of the directivity index on frequency for a reflex microphone, an organ type microphone and a microphone array with their limited dimensions, as well as the dependence of spatial selectivity on the aperture at fixed frequencies, is carried out. A design scheme is proposed for a small-sized acoustic reconnaissance device based on a microphone array using microelectromechanical microphone systems technology, with a hypercardioid type of radiation pattern, and an over-directivity algorithm, which is a combination of a differential algorithm and a delay and sum algorithm. The optimal step between the microphones in the array was calculated at the set maximum working frequency of 10 kHz, the number of single microphones was calculated for the overall dimensions of the acoustic reconnaissance equipment of 30 cm and 10 cm. The use of the selected type of narrow-directional microphone with the proposed algorithm for digital signal processing leads to an increase in the directivity index of the microphone array to the level of the reflex microphone, which can significantly reduce the size (from 30 cm to 10 cm) and the number of microphones (from 12 to 4) design while maintaining spatial selectivity.